The effect of vesicular arbuscular mycorrhizal inoculation on nutrient uptake and yield of alley cropped cassava in a degraded Alfisol of southwestern Nigeria - Osonubi, O.; Atayese, M.O.; Mulongoy, K. (1995)
Leaf and root (tuber) nutrient uptake patterns of cassava (Manihot esculenta Crantz) alley-cropped with gliricidia (Gliricidia sepium), leucaena (Leucaena leucocephala), and senna [(Senna (syn. Cassia) siamea] as influenced by vesicular-arbuscular mycorrhizal (VAM) inoculation in a degraded Alfisol were investigated in consecutive years. The cassava plants were mulched with fresh prunings of each hedgerow tree species at 2-month intervals in the second and third years of alley cropping. While VAM inoculation significantly influenced the root uptake of nutrients, the leaf uptake was not affected except for the uptake of P. In most cases, there was no difference in the nutrient concentration between inoculated and uninoculated plants, either in the leaf or in the root, indicating that the productivity of cassava was regulated by the amount of nutrients the roots could absorb. In spite of similar total soil N in all inoculated and uninoculated alley-cropped cassava plots and similar exchange-able soil K contents in inoculated and uninoculated alley-cropped cassava plots with leucaena and senna, greater uptake of N, P, and K and greater concentrations of K were observed in roots of inoculated alley-cropped cassava with gliricidia and leucaena than with senna. These results indicated that greater mineralization and availability of nutrients to cassava roots from prunings of nodulating gliricidia and leucaena than from non-nodulating senna may be important, particularly with efficient VAM inoculation, in these alley-cropping systems. Also, for similar nutrients in the inoculated and uninoculated cassava soils alley-cropped with each hedgerow species, VAM inoculation significantly enhanced cassava root dry weights, indicating that an effective VAM fungus can be an agent of greater nutrient uptake in a competitive environment.